(untitled) (Journal of European Studies (JES), 2018)
Britain has always been a land of several ethno-national groups. As an imperial power, it ruled over several nations in Asia and Africa. The British Empire unraveled after the Second World War ended in 1945, and Britain was left with an economy and infrastructure in shambles. To revive the British economy, immigrants were taken in from diverse backgrounds, mostly from Britain’s former colonies. To accommodate these migrants and to avoid racial tensions, the policy of multiculturalism was designed and adopted. Over the decades, British multiculturalism has been confronted with several challenges and the prominent British political parties have responded to them in different ways. The aim of this paper is to analyze and compare the respective policies of major political parties on multiculturalism. The focus of the study is on the period 1997-2016, for during this particular period, debate began on multiculturalism. The debate became more contentious in the aftermath of the catastrophic events of 9/11and the 7/7 London bombings.